2023
DOI: 10.1007/s11240-023-02485-8
|View full text |Cite
|
Sign up to set email alerts
|

Methyl jasmonate and salicylic acid as powerful elicitors for enhancing the production of secondary metabolites in medicinal plants: an updated review

Abstract: Plant secondary metabolites are bioactive scaffolds that are crucial for plant survival in the environment and to maintain a defense mechanism from predators. These compounds are generally present in plants at a minimal level and interestingly, they are found to have a wide variety of therapeutic values for humans. Several medicinal plants are used for pharmaceutical purposes due to their affordability, fewer adverse effects, and vital role in traditional remedies. Owing to this reason, these plants are exploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 110 publications
3
15
0
Order By: Relevance
“…Moradi et al's [22] exploration of MJ's impact on h6h, PMT1, and PMT2 expression in chamomile plants also provides a parallel to our findings, where h6h expression remained unchanged in the leaves, and PMT expression was detected in both treated and untreated leaves. The differences in gene expression and alkaloid accumulation between the studies could be due to the different treatment durations and the inherent interspecies variability in response to MJ.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Moradi et al's [22] exploration of MJ's impact on h6h, PMT1, and PMT2 expression in chamomile plants also provides a parallel to our findings, where h6h expression remained unchanged in the leaves, and PMT expression was detected in both treated and untreated leaves. The differences in gene expression and alkaloid accumulation between the studies could be due to the different treatment durations and the inherent interspecies variability in response to MJ.…”
Section: Discussionsupporting
confidence: 89%
“…The current study's findings on the impact of MJ on tropane alkaloid biosynthesis in D. stramonium offer a nuanced perspective compared to previous research. The observed increase in atropine and decreased scopolamine in the roots after MJ treatment align with Moradi et al's findings [22], which suggested that 150 µM MJ was optimal for producing alkaloids in henbane hairy roots. However, the lack of significant changes in scopolamine levels in the leaves in the present study contrasts with Moradi et al's [22] results, where scopolamine levels increased (Dubey et al, 2021) [43].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Foliar monoterpene and sesquiterpene emissions from many plant species increase after MeJA application (Wuyun et al, 2023;Cappellari et al, 2019). MeJAmediated elicitation is utilized in many commercial strategies for the overproduction of naturally active plant products (Jeyasri et al, 2023). Wounding induces the synthesis of jasmonate, which mediates the defence response in plants (Turner et al, 2002).…”
Section: Identification Of Transcripts and Their Expression Analysismentioning
confidence: 99%